2014
DOI: 10.1007/s11695-013-1169-7
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Results of Laparoscopic Sleeve Gastrectomy and Roux-en-Y Gastric Bypass in Adolescent Patients

Abstract: The prevalence and severity of obesity in children and adolescents has been increasing in recent years at an unprecedented rate. Morbidly obese children will almost certainly develop severe comorbidities as they progress to adulthood, and bariatric surgery may provide the only alternative for achieving a healthy weight. The aim of this study was to assess the long-term outcomes and safety of laparoscopic sleeve gastrectomy (LSG) and Roux-en-Y gastric bypass (RYGB) as new treatment modalities for morbidly obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The majority of studies were from the USA, only three were from Europe, i.e., Austria [ 34 ], Portugal [ 35 ], and Sweden [ 36 ]. Six studies reported data on 173 adolescent patients before bariatric surgery with the number of patients ranging from 10 to 40 [ 34 , 36 , 37 , 38 , 39 , 40 ]; six studies reported data on 227 adolescent patients after bariatric surgery with the number of patients ranging from 10 to 101 [ 35 , 36 , 41 , 42 , 43 , 44 , 45 ]. The gender in all studies was predominantly female, except for one [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies were from the USA, only three were from Europe, i.e., Austria [ 34 ], Portugal [ 35 ], and Sweden [ 36 ]. Six studies reported data on 173 adolescent patients before bariatric surgery with the number of patients ranging from 10 to 40 [ 34 , 36 , 37 , 38 , 39 , 40 ]; six studies reported data on 227 adolescent patients after bariatric surgery with the number of patients ranging from 10 to 101 [ 35 , 36 , 41 , 42 , 43 , 44 , 45 ]. The gender in all studies was predominantly female, except for one [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study designs varied between retrospective reviews of clinical charts of patients [ 37 , 38 , 39 , 40 , 45 ], clinical follow-ups after examinations have been carried out [ 34 , 41 ], and prospective feasibility, safety or observational studies [ 35 , 36 , 42 , 43 , 44 ]. Surgical procedures were either LAGB [ 34 , 35 , 37 , 41 , 42 ] or RYGB [ 36 , 39 , 43 , 44 , 45 ] or were not specified [ 38 , 40 ]. Most studies dealt with depressive disorders and depressive disorder symptoms in bariatric surgery patients, while one [ 36 ] described depressive and anxiety disorder symptoms from a pre- and post-operative point of view and another reported on pre-operative eating disorder symptoms [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in earlier studies like the one that Cozacov published in 2014, show the comparable efficiency of RYGB and sleeve gastrectomy in enabling weight loss in adolescents with obesity with similar rates of comorbidity resolution. The author's preference for sleeve gastrectomy seems motivated by the simplicity of the surgical procedure -absence of anastomosis, the restrictive component that comes with serious stomach volume reduction and the hormonal down regulation of hunger hormones induced by stomach partial resection, that results in a long-term reduction of hunger feeling (18).…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss surgery is now considered the most effective treatment for morbidly obese adults [28]. Studies on the efficacy of bariatric surgery in adolescent patients have shown promising results with profound short term and sustained long term weight loss [9,10,13,15,17,20,21,24,25,[29][30][31][32][33][34][35][36][37][38].…”
Section: Linear Regression Analysis For Seromarkers Associated With Omentioning
confidence: 99%